Inclusive Education in Practice: Exploring Teachers' Struggles in Far-West Province in Nepal (Surkhet Journal, 2025)
This study explores the challenges faced by teachers in teaching students with physical disabilities. Using an explorative qualitative case study design, data were collected through in-depth interviews with three physically disabled teachers in an inclusive school in Kailali district. The study identifies five key challenges related to the teaching and learning process for physically disabled students, such as a lack of disability-assistive infrastructure, limited parental support, financial constraints, inadequate teacher training and instructional materials, and personal and individual challenges. These multiple factors hinder not only the learning of disabled students but also the creation of an inclusive and supportive learning environment. The study concludes that addressing these challenges demands collaborative efforts from policymakers, stakeholders, researchers, and educators to ensure equitable access to quality education for all students, regardless of their physical abilities. The study suggests the need for comprehensive targets such as investments in specialized teacher training and resources, infrastructure, and instructional materials, along with initiatives to enhance community and parental engagement in the educational process, tailored to the diverse needs of students with physical disabilities.